Security management of national park security in the border of Indonesia - Malaysia - Saptono, Edy; Keiza, Ribka; Wijayanto, Joni (Technium Social Sciences Journal, 2021)
Boundary is an important part of the state’s sovereignty and becomes a fortress of all kinds of threats. The threat about security of natural resources is one of non-military threat which affects Indonesia’s security. Betung Kerihun National Park adjoins to Malaysia in northern of Indonesia, so it can be vulnerable to threats. The purposes of this research are to analyze the threat of security toward management of Betung Kerihun National Park (TNBK), the efforts made to overcome the security threat, and the management of TNBK on the border of Indonesia and Malaysia. The research uses qualitative method using in-depth interviews and later analyzing the primary and secondary data. The results show that the security threats of TNBK are agarwood stealing, gold mining, illegal logging, wildlife distribution, lack of security staff, no security forces (Satgas Pamtas) on the northern boundary of TNBK, and border patrol inspection line construction. The efforts to overcome security threats are preventive, pre-emptive, and repressive. The management of TNBK on the border of Indonesia and Malaysia in order to protect border security are including management functions of planning, organizing, leading (directing), and evaluating. The recommendations to overcome the security threat of national parks on the border between Indonesia and Malaysia are the active role of security forces and the establishment of buffer zone management.